Admission Levels of DKK1 (Dickkopf-1) Are Associated With Future Cardiovascular Death in Patients With Acute Coronary Syndromes: Insights From the PLATO Trial. Issue 2 (February 2019) - Ueland, Thor; Åkerblom, Axel; Ghukasyan, Tatevik; Michelsen, Annika E.; Becker, Richard C.; Bertilsson, Maria; Himmelmann, Anders; James, Stefan K.; Siegbahn, Agneta; Storey, Robert F.; Kontny, Frederic; Aukrust, Pål; et al.
Abstract : Objective—: The Wnt/wingless signaling antagonist DKK1 (dickkopf-1) regulates platelet-mediated inflammation and may contribute to plaque destabilization. We hypothesized that DKK1 would be associated with cardiovascular outcomes. Approach and Results—: We determined DKK1 levels in serum samples obtained before randomization, at discharge, and 1 and 6 months in a subset of 5165 patients with acute coronary syndromes in the PLATO trial (Platelet Inhibition and Patient Outcomes; NCT00391872). The median (interquartile range) DKK1 concentrations were 0.61 (0.20–1.27) ng/mL at baseline and increased during follow-up. The hazard ratio (95% CIs) for the composite end point (cardiovascular death, nonprocedural spontaneous myocardial infarction, or stroke) during 1 year of follow-up, per 50% increase in baseline DKK1 concentration, was 1.06 (1.02–1.10), P =0.0011, and remained significant in fully adjusted analysis with 14 conventional clinical and demographic and 6 biochemical variables, including NT-proBNP (N-terminal pro-B-type natriuretic peptide), hs-TnT (high-sensitivity troponin T), and GDF-15 (growth differentiation factor 15; 1.05 [1.00–1.09]; P =0.028). This association was mainly driven by the association with cardiovascular death, where a gradual increase in event rates was observed with increasing quartiles of DKK1 (2.7%, 3.0%, 4.3%, and 5.0%) and remained significant and unmodified in fully adjusted analysis (hazard ratio, 1.10 [1.04–1.17]; P =0.002). Change in DKK1 and levels at 1 month were unrelated to outcomes. A modifying effect of ticagrelor on DKK1 discharge levels was observed but not associated with prognosis. Conclusions—: In patients with acute coronary syndromes treated with dual antiplatelet treatment, admission DKK1 levels were independently associated with a composite of cardiovascular death, myocardial infarction, or stroke and with cardiovascular death alone. Abstract : Supplemental Digital Content is available in the text.